Real World Data of Response of Trastuzumab Based Chemotherapy in Locally Advanced HER2 Positive Breast Cancer from a Developing Country - Chandra Doval, Dinesh; Bothra, Sneha; Goyal, Pankaj; Agrawal, Chaturbhuj; Jain, Parveen; Tripathi, Rupal; Sharma, Anurag; Pasricha, Sunil; Choudhary, Kumardeep Dutta (Asian Pacific Journal of Cancer Care, 2021)
Background: Data regarding pathologic response of Trastuzumab based chemotherapy in locally advanced HER2 positive breast cancer in neoadjuvant setting is scarce. Methods: A retrospective analysis was conducted from January 2014 to January 2019 at a tertiary cancer care centre in North India and 81 breast cancer patients who underwent neoadjuvant chemotherapy were included. The clinical and pathologic characteristics, response, toxicity and survival data was collected, collated and analyzed. Results: The most commonly observed tumor characteristics at baseline were clinical stage T4 (72.8%), nodal stage N2 (40.7%), invasive ductal carcinoma on histology (98.8%), grade 3 (66.7%) and hormone receptor negativity (54.3%). In terms of post treatment characteristics, a higher incidence of partial response (55.6%), post treatment tumor stage ypT0 (45.7%), nodal status ypN0 (54.3%), absence of extracapsular invasion (77.8%) and absence of pathologic complete response (pCR, 63%) were observed. pCR was attained in 30 patients and was most commonly associated with clinical tumor stage T4 (26/30), nodal stage N2-N3 (19/30), grade 3 (21/30) and hormone receptor negativity (20/30). Altogether, 19.75% had grade 3/4 adverse events. At 6 years, 86% v/s 61% patients were disease free (p=0.037) and 93% v/s 79% patients (p=0.181) were alive in the pCR and no pCR groups, respectively. Conclusion: Even in locally advanced breast cancer (LABC), Trastuzumab had good response in terms of pCR and survival outcomes. Thus, one can be encouraged to use this single HER2 blockade if dual blockade is not feasible in HER2 positive LABC in the neoadjuvant setting.